«A WHITE BOY IN A WHITE SHIRT WAS WEEPING»: PSYCHOANALYTICAL STUDIES ON VASYL STEFANYK’S CREATIVITY - Yurchuk, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Exceptional life and peculiar personality of Vasyl Stefanyk very often has been the factual basis for biographical novels. The proposed research focuses on psychobiographical novel Stepan Protsiuk’s «The Rose of Ritual Pain» where the writer offers the author’s version of the psychobiographical portrait of Vasyl Stefanyk, focusing on the «inner biography» of the artist.